The theory-practice gap of project appraisals - Nur Adiana Hiau Abdullah; Sabariah Norin (Penerbit Universiti Kebangsaan Malaysia, 2008)
This paper is intended to examine the capital budgeting practices of listed companies in Malaysia. A comparison is made between the Main Board and Second Board companies with respect to the techniques used in evaluating major capital investment projects. In achieving the intended purpose, 356 questionnaires were sent to companies listed on the Main Board and 254 to the Second Board of nine industrial sectors of Bursa Malaysia. Descriptive and inferential statistics were used to analyze the data. The results of the study indicate prevalent use of the payback and the accounting rate of return (ARR) techniques in evaluating major capital investment projects. This is followed by the net present value (NPV) and the internal rate of return (IRR) methods. Large and small companies in an emerging market such as Malaysia prefer a simpler and less sophisticated technique in the assessment of major investment projects. This is inconsistent to the proposition that the theory-practice gap has narrowed in recent years. As for the non financial criteria 22.9% of the Main Board companies used such evaluation in their project assessments. This is not observed in the Second Board companies which are considered to be smaller than the Main Board companies. With respect to the usage frequency of the financial analysis techniques, the more complicated the technique, such as the IRR, the higher are the percentages of the smaller companies not using or rarely used the method.